Individual markers of cerebral small vessel disease and domain‐specific quality of life deficits. Issue 5 (10th March 2021) - Fernando, Jeevan; Brown, Robin B.; Edwards, Hayley; Egle, Marco; Markus, Hugh S.; Tay, Jonathan
Abstract: Background: Cerebral small vessel disease (SVD) leads to reduced quality of life (QOL), but the mechanisms underlying this relationship remain unknown. This study investigated multivariate relationships between radiological markers of SVD and domain‐specific QOL deficits, as well as potential mediators, in patients with SVD. Methods: Clinical and neuroimaging measures were obtained from a pooled sample of 174 SVD patients from the St. George's Cognition and Neuroimaging in Stroke and PRESsure in established cERebral small VEssel disease studies. Lacunes, white matter hyperintensities, and microbleeds were defined as radiological markers of SVD and delineated using MRI. QOL was assessed using the Stroke‐Specific Quality of Life Scale. Multivariate linear regression was used to determine whether SVD markers were associated with domain‐specific QOL deficits. Significant associations were further investigated using mediation analysis to examine whether functional disability or cognition was potential mediators. Results: Multivariate regression analyses revealed that lacunes were associated with total QOL score ( β  = −8.22, p  = .02), as well as reductions in mobility ( β  = −1.41, p  = .008) and language‐related subdomains ( β  = −0.69, p  = .033). White matter hyperintensities and microbleeds showed univariate correlations with QOL, but these became nonsignificant during multivariate analyses. Mediation analyses revealed that functional disability, defined as reduced activities of daily living, and executive function, partially mediated the relationship between lacunes and total QOL, as well as mobility‐related QOL, but not language‐related QOL. Conclusions: Lacunar infarcts have the most detrimental effect on QOL in SVD patients, particularly in the mobility and language‐related subdomains. These effects may be partially explained by a reduction in activities of daily living. These results may inform targeted interventions to improve QOL in patients with SVD. Abstract : Fernando et al. investigate associations between radiological markers of cerebral small vessel disease (SVD) and subdomains of quality of life (QOL). In a pooled sample of SVD patients, they find that lacunes lead to reductions in total QOL, as well as mobility and language‐related QOL, and explore potential mediating variables. These results suggest the possibility of targeted interventions to improve QOL in SVD patients.